Aspek Hukum Terhadap Perjanjian Jual-Beli Rumah Secara Kredit Kepemilikan Rumah (KPR) di Perum-Perumnas Terhadap Konsumen (Studi di Perum Perumnas) - Ronny Malemta Ginting; Marsella Marsella; Wessy Trisna (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
In this era, the government pays more attention to improving people's welfare, especially low-income groups, because low-income is one of the most common jobs in Indonesia today. Subsidized Home Ownership Loans (KPR) are loans provided by banks and are part of a government program. The subsidy will depend on the level of credit or down payment. Number according to law. Presidential Decree No. 1 of 2011 concerning Housing and Settlements, low-income communities receive home ownership support through facilitation policies and/or help build and buy houses. The formulation of the problem in this thesis is how the legal procedure for the house sale and purchase agreement with home ownership credit (KPR) at PERUM PERUMNAS and what form of settlement, if there is a default on the home sale and purchase agreement on home ownership credit (KPR) at PERUM PERUMNAS. The legal research method used is normative juridical which is descriptive. The research location was conducted at PERUM PERUMNAS MARTUBUNG PERUM-PERUMNAS MEDAN (GRIYA MARTUBUNG) Jalan Tuar Raya No. 03 Griya Martbung, (20252) Medan. The data used consists of primary and secondary data. The data was collected by the method of literature study and field study. The data that has been collected was analyzed qualitatively. The nature of the research conducted is the nature of the research with descriptive analysis. Based on the results of the author's research, what is done is the legal procedure for the home sale and purchase agreement by means of a home ownership loan (KPR) at PERUM PERUMNAS, which is carried out by a credit agreement and a form of settlement, in the event of a default on the buying and selling activities of a house on a home ownership credit (KPR). at PERUM PERUMNAS, namely conducting an auction.